Cell Surface Antigen Induced by Influenza Virus - Hahon, Nicholas (1972)
By immunofluorescence staining, a specific surface antigen induced by influenza virus was detected on clone 1-5C-4 cells. The antigen was neither related to hemagglutinin nor dependent on the production of infectious virus. Formation of the virus-specific cell surface antigen was dependent on protein synthesis but independent of viral ribonucleic acid replication.